The Role of Capital Market Notary in Corporate Backdoor Listing Actions in Indonesia - Nabilla Syahdinda; Arman Nefi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The Rapid of economic development certainly affects the business world seen from the efforts of a company to expand its business, where business expansion certainly requires large funding. One of the ways to obtain funding is through activities in the capital market. A Limited Liability Company will trade securities but previously the company must have been listed on the Stock Exchange. The mechanism of going public by way of an Initial Public Offering (IPO) has conditions that are difficult to fulfill for some companies, so some companies take an alternative by doing Backdoor Listings, in order to be listed and get benefits like a public company. The author uses a normative juridical approach by examining literature or secondary data related to tertiary legal principles and norms and materials, which will be analyzed descriptively. The author sees that, there is no specific regulation related to backdoor listing corporate actions in the implementation of capital market activities in Indonesia and likewise with the absence of regulations that can be used as guidelines by notaries in the capital market sector in supporting backdoor listing corporate actions.`Keywords: Backdoor Listing, Notary, IPO, Go Public, the Financial Services Authority